HUBUNGAN ANTARA MINAT BACA DENGAN KEMAMPUAN LITERASI PADA SISWA KELAS IV SD NEGERI SUNGGUMINASA V - Syam, Wahdinah; Nur Fadhilah, Azizah; NurJannah, Fadyah; Faisal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Literacy skills in Indonesia still face significant challenges, as demonstrated by the results of the 2022 PISA survey, which placed Indonesia at a low position. Low literacy is often associated with reading interest, but previous research has shown inconsistent results. This study aims to analyze the relationship between reading interest and literacy skills in fourth-grade students of SD Negeri Sungguminasa V. This study used a quantitative approach with a correlational design and a total sampling technique involving 25 students. Data were collected through a reading interest questionnaire and an objective literacy ability test. Data analysis was conducted descriptively and inferentially using the Spearman's Rho correlation test because the data were not normally distributed. The results showed that the average reading interest score was 37.24 and literacy ability was 12.88. The correlation test produced a coefficient of 0.214 with a significance value of 0.305 (p > 0.05), indicating a weak and insignificant relationship. Thus, it was concluded that there was no significant relationship between reading interest and literacy skills in the study subjects.